2010
DOI: 10.1021/cr1000783
|View full text |Cite
|
Sign up to set email alerts
|

Defect-Mediated Trafficking across Cell Membranes: Insights from in Silico Modeling

Abstract: He graduated from St. Petersburg State University (Russia), where he was trained as a theoretical physicist. After receiving his Ph.D. from the Institute of Macromolecular Compounds in 1999, he spent several years working in the Theoretical Polymer Group of Prof. A. Blumen (University of Freiburg, Germany), in the Biophysics and Soft Matter Group of Prof.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
173
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 171 publications
(189 citation statements)
references
References 249 publications
13
173
0
1
Order By: Relevance
“…Therefore, it is suggested that the groove we see is a pathway for transport of lipid from the exoplasmic side to a cytoplasmically facing exit site situated approximately at the location of the PE molecule in SERCA. MD simulations have indicated that lipid translocation (flip-flop) across a lipid bilayer is enhanced by the presence of packing defects creating water pores in the bilayer (36). In analogy, it has been proposed that the phospholipid scramblase activity of serpentine receptors, such as rhodopsin and the β-adrenergic receptor, owes to the presence of a string of water molecules in the protein interior that interact with the hydrophilic head groups of phospholipids during transfer across the bilayer interior (26).…”
Section: Hydrophobic Residues Adjacent To I364 Display Mutational Senmentioning
confidence: 99%
“…Therefore, it is suggested that the groove we see is a pathway for transport of lipid from the exoplasmic side to a cytoplasmically facing exit site situated approximately at the location of the PE molecule in SERCA. MD simulations have indicated that lipid translocation (flip-flop) across a lipid bilayer is enhanced by the presence of packing defects creating water pores in the bilayer (36). In analogy, it has been proposed that the phospholipid scramblase activity of serpentine receptors, such as rhodopsin and the β-adrenergic receptor, owes to the presence of a string of water molecules in the protein interior that interact with the hydrophilic head groups of phospholipids during transfer across the bilayer interior (26).…”
Section: Hydrophobic Residues Adjacent To I364 Display Mutational Senmentioning
confidence: 99%
“…It is therefore not surprising that the molecular mechanism of pore formation in zwitterionic lipid membranes was repeatedly demonstrated to be qualitatively similar in both cases, supporting thereby its generic nature. 5,18 In particular, it was shown that the pore formation process is largely driven by the appearance and growth of a water defect spanning the membrane, 4,11,20 which is finalized by a considerable reorientation of lipid head groups toward the membrane interior. 4,10,12 Such hydrophilic pores were proved to serve as permeation pathways for ions 21 and nuclear acids.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 Membrane pores can also be chemically induced by the use of particular membrane-fluidizing compounds such us dimethyl sulfoxide (DMSO, (CH 3 ) 2 SO), a small amphiphilic molecule that has been shown to enhance cell permeability through the formation of water pores. 4,5 Recently, molecular dynamics (MD) simulations have been used to elucidate the molecular mechanisms leading to pore formation in simple lipid bilayers by both the application of an external electric field [6][7][8][9][10] and the effects of DMSO. 5,[10][11][12] According to the simulations, the molecular mechanism of electroporation occurs in different stages.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 Recently, molecular dynamics (MD) simulations have been used to elucidate the molecular mechanisms leading to pore formation in simple lipid bilayers by both the application of an external electric field [6][7][8][9][10] and the effects of DMSO. 5,[10][11][12] According to the simulations, the molecular mechanism of electroporation occurs in different stages. First, the disordering of the water molecules at the membrane interface due to the applied field eventually generates a water defect/intrusion that initiates pore formation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation